European Junior Championships as a prerequisite for Olympic success in swimming - Toner, C.; Mooney, R.; Swanton, A. (Journal of Human Sport & Exercise, 2017)
Current research has focused on athlete career trajectories and how this can be used a form of talent identification. According to Abernethy 2008, countries are attempting to develop structures to identify exceptionally gifted athletes as early as possible so they can focus available resources on promising individuals and promote their development in a sport. Research on career trajectories in swimming carried out by Allen et al., 2014, highlighted that a pathway towards elite performance is a critical factor in talent identification. This paper aims to establish: (i) the number of European Junior (EJ) athletes who progressed to Olympics, (ii) is a EJ medallist more likely to compete/medal at the Olympics. A user friendly database was created in MS Excel to analyse large amounts of data extracted from Swimrankings.net. Data was gathered from Men`s 50/100/200/400/1500 Freestyle events ranging from 2001 to 2012. Results highlight that 25% of European Junior finalists transition to the Olympics, with 45% of medallists making this transition. 5% of athletes who finaled at EJ went on to medal at the Olympics. One Some key findings from this study so far: ten athletes who have medalled at Olympics in the chosen events nine also medalled at EJ. Eight of these athletes medalled in the same event at the Olympics as they did at EJ. A further analysis of male and female events in is on-going at present.